Bacterial Diversity of Intestinal Microbiota in Patients with Substance Use Disorders Revealed by 16S rRNA Gene Deep Sequencing - Yu Xu (Nature Portfolio, 2017)
Abstract Substance abuse and addiction are worldwide concerns. In China, populated with over 1.3 billion people, emerging studies show a steady increase in substance abuse and substance-related problems. Some of the major challenges include a lack of an effective evaluation platform to determine the health status of substance-addicted subjects. It is known that the intestinal microbiota is associated to the occurrence and development of human diseases. However, the changes of bacterial diversity of intestinal microbiota in substance-addicted subjects have not been clearly characterized. Herein, we examined the composition and diversity of intestinal microbiota in 45 patients with substance use disorders (SUDs) and in 48 healthy controls (HCs). The results show that the observed species diversity index and the abundance of Thauera, Paracoccus, and Prevotella are significantly higher in SUDs compared to HCs. The functional diversity of the putative metagenomes analysis reveals that pathways including translation, DNA replication and repair, and cell growth and death are over-represented while cellular processes and signaling, and metabolism are under-represented in SUDs. Overall, the analyses show that there seem to be changes in the microbiota that are associated with substance use across an array of SUDs, providing fundamental knowledge for future research in substance-addiction assessment tests.